2023
DOI: 10.3390/horticulturae9060639
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Applications of Oxalic Acid and Salicylic Acid Increase Fruit Firmness and Polyphenolic Content in Blueberry (Vaccinium corymbosum L.)

Jorge Retamal-Salgado,
Geber Adaos,
George Cedeño-García
et al.

Abstract: Blueberry exports that imply transport times of more than 25 d deteriorate their quality. The use of elicitors in preharvest has shown positive effects on the quality of berries such as grapes. The objective of this study was to evaluate preharvest applications (21, 14, and 7 d before harvest) of oxalic acid (OA) and salicylic acid (SA) on fruit firmness and phenolic compounds in blueberry. The treatments of 0, 2, and 4 mM OA in ‘Kirra’ and 0, 2, and 4 mM SA are in ‘Stella blue’. With the earlier preharvest ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…As for leaf temperature, the results indicate that the different mulches did not have a significant effect. This suggests that the ambient temperature in the study area, with maximums of up to 30 • C at the time of the measurements, may not have been a determining factor in this parameter [41]. However, when analyzing the soil surface temperature, it was observed that the GEO mulch showed a higher temperature compared with the control, while it presented similarity in this aspect with the other mulching treatments.…”
Section: Weeds Soil Moisture and Temperature And Leaf Temperaturementioning
confidence: 86%
“…As for leaf temperature, the results indicate that the different mulches did not have a significant effect. This suggests that the ambient temperature in the study area, with maximums of up to 30 • C at the time of the measurements, may not have been a determining factor in this parameter [41]. However, when analyzing the soil surface temperature, it was observed that the GEO mulch showed a higher temperature compared with the control, while it presented similarity in this aspect with the other mulching treatments.…”
Section: Weeds Soil Moisture and Temperature And Leaf Temperaturementioning
confidence: 86%
“…Our results agree with Giménez et al [ 45 ], who showed that 0.5 mM SA application significantly increased TP (by about 20%) and AA (by about 50%) in fruits of P. avium . Recently, Retamal-Salgado et al [ 51 ] showed that 2 mM SA application increased by 100% TP, AA and ANT in V. corymbosum fruits. In contrast, we did not observe changes in ANT between SA treatments in DI plants.…”
Section: Discussionmentioning
confidence: 99%